EKSPLORASI ETNOMATEMATIKA PADA MAKANAN TRADISIONAL KHAS BANTEN - Siti Rohimah; Agung Wintoro, Mutmainah Shafira Salsabilah, Aji Setyo Pambudi (CV. ADIBA AISHA AMIRA, 2024)
Ethnomathematic explains or teaches about mathematics related to culture. One of them is traditional Banten food. The purpose of this study is to describe ethnomathematics and identify mathematical concepts in traditional Banen food in the Serang City. The research method used in this research is qualitative. Data collection techniques used through observation, interviews, and documentation. Data analysis techniques to process data in research are data reduction, data presentation, and drawing conclusions. The results showed that there are mathematical concepts in the form of traditional Banten food, namely geometric elements such as circles,blocks, cones and parallelogram.